BIODIESEL PRODUCTION FROM PALM OIL OVER SYNTHESIZED CERIA NANOMATERIALS - OLUWASEGUN, OYENUBI ABAYOMI (2017)
Many high yielding catalyst ranging from homogenous, heterogeneous and biocatalysts have been used for biodiesel production. However, high amount of energy is still required to mix the reactants (oils and alcohols) during reactions. Therefore, this study examine four ceria nanomaterials that are capable of increasing miscibility by lowering the surface tension at the interface of the reactants. The synthesized ceria nanomaterials namely; titanium doped ceria, cerium dodecyl trimethyl ammonium bromide, cerium hexadecyl trimethyl ammonium bromide and cerium hexadecyl trimethyl ammonium chloride were characterized by x-ray diffraction techniques (XRD), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy and surface area and pore size analyzer. After which they were used for transesterification of palm oil. A 0.4 wt. % CeO2-TiO2 gave a yield of 70.6 % at 55 ◦C, 12:1 methanol oil ratio, and 1.0 wt. % catalyst loading in 150 minutes. The density and viscosity of biodiesel produced are 920.9 kg/m3 and 12 N.s/m2 respectively. Cerium dodecyl tri ethyl ammonium bromide with particle size ranging between 22 – 33 nm achieved a maximum triglyceride conversion of 89.77 % at 65 oC temperature, 6:1 methanol oil ratio, 2.5% catalyst loading and reaction time of 6 hours. Cerium hexadecyl trimethyl ammonium bromide and cerium hexadecyl trimethyl ammonium chloride achieved 92.58% and 99.29% conversion at same reaction condition. Kinetic study showed that the activation energy and frequency factor of the transesterification process using the best catalyst was 41.38 kJK-1mol-1 and 1.6 × 106 min-1 respectively.